Fourier Serie
Fourier Serie
Fourier Serie
Note: The knowledge of odd and even functions can save a lot of unnecessary calculations
Product of odd and even functions:
Odd × Odd=Even, Even × Even=Even, Odd × Even =Odd
0 if f ( x) is odd
c
c
Also, f ( x) dx
c 2 f ( x) dx if f ( x) is even
0
Problems:
𝑥
1. Determine the Fourier series for the function 𝑓(𝑥) = 2 , 0 < 𝑥 < 2𝜋 and 𝑓(𝑥 + 2𝜋) = 𝑓(𝑥).
Sol.
2 𝑐+𝑇
𝑎0 = ∫ 𝑓(𝑥) 𝑑𝑥
𝑇 𝑐
2 2𝜋 𝑥
𝑎0 = ∫ 𝑑𝑥
2𝜋 0 2
2
2
1 x
a0 .
2 2
0
1 4𝜋 2
𝑎0 = [ − 0]
2𝜋 2
∴ 𝑎0 = 𝜋
2 𝑐+𝑇 2𝑛𝜋𝑥
𝑎𝑛 = ∫ 𝑓(𝑥) cos ( ) 𝑑𝑥
𝑇 𝑐 𝑇
2 2𝜋 𝑥
𝑎𝑛 = ∫ cos 𝑛𝑥 𝑑𝑥
2𝜋 0 2
1 2𝜋
𝑎𝑛 = ∫ 𝑥 cos 𝑛𝑥 𝑑𝑥
2𝜋 0
1 𝑥 sin 𝑛𝑥 2𝜋 1 2𝜋
𝑎𝑛 = {[ ] − ∫ sin 𝑛𝑥 𝑑𝑥}
2𝜋 𝑛 0 𝑛 0
1 1
𝑎𝑛 = {(0 − 0) − (0)} = 0
2𝜋 𝑛
∴ 𝑎𝑛 = 0.
2 𝑐+𝑇 2𝑛𝜋𝑥
𝑏𝑛 = ∫ 𝑓(𝑥) sin ( ) 𝑑𝑥
𝑇 𝑐 𝑇
2 2𝜋 𝑥
𝑏𝑛 = ∫ sin 𝑛𝑥 𝑑𝑥
2𝜋 0 2
1 2𝜋
𝑏𝑛 = ∫ 𝑥 sin 𝑛𝑥 𝑑𝑥
2𝜋 0
1 𝑥 cos 𝑛𝑥 2𝜋 1 2𝜋
𝑏𝑛 = {[− ] − ∫ − cos 𝑛𝑥 𝑑𝑥}
2𝜋 𝑛 0 𝑛 0
1 2𝜋 1 1
𝑏𝑛 = {(− cos 2𝑛𝜋 − 0) + (0)} = − ∵ cos 2𝑛𝜋 = 1
2𝜋 𝑛 𝑛 𝑛
1
∴ 𝑏𝑛 = −
𝑛
The Fourier series is given by,
∞ ∞
𝑎0 2𝑛𝜋𝑥 2𝑛𝜋𝑥
𝑓(𝑥) = + ∑ 𝑎𝑛 cos ( ) + ∑ 𝑏𝑛 sin ( )
2 𝑇 𝑇
𝑛=1 𝑛=1
∞
𝜋
𝑓(𝑥) = + ∑ 𝑏𝑛 sin(𝑛𝑥)
2
𝑛=1
𝜋 1 1 1
𝑓(𝑥) = + {− sin 𝑥 − sin 2𝑥 − sin 3𝑥 − ⋯ }
2 1 2 3
𝜋 1 1
∴ 𝑓(𝑥) = − {sin 𝑥 + sin 2𝑥 + sin 3𝑥 + ⋯ }
2 2 3
2. Obtain the Fourier series expansion for the function 𝑓(𝑥) = 𝑥 2 , −𝜋 < 𝑥 < 𝜋.
Sol. We have 𝑓(𝑥) = 𝑥 2 . 𝑓(𝑥) is an even function. Therefore 𝑓(𝑥) contains only cosine terms. Hence 𝑏𝑛 = 0.
2 𝑐+𝑇 2 𝜋 2
𝑎0 = ∫ 𝑓(𝑥) 𝑑𝑥 = ∫ 𝑥 𝑑𝑥
𝑇 𝑐 2𝜋 −𝜋
𝜋
1 𝑥3 1 3 3
2𝜋 3
𝑎0 = [ ] = [𝜋 − (−𝜋 )] =
𝜋 3 −𝜋 3𝜋 3𝜋
2
2𝜋
∴ 𝑎0 =
3
2 𝑐+𝑇 2𝑛𝜋𝑥
𝑎𝑛 = ∫ 𝑓(𝑥) cos ( ) 𝑑𝑥
𝑇 𝑐 𝑇
2 𝜋 2 2 𝜋
𝑎𝑛 = ∫ 𝑥 cos 𝑛𝑥 𝑑𝑥 = ∫ 𝑥 2 cos 𝑛𝑥 𝑑𝑥
2𝜋 −𝜋 𝜋 0
2 2𝜋
𝑎𝑛 = [0 + 2 cos 𝑛𝜋 + 0]
𝜋 𝑛
4
∴ 𝑎𝑛 = (−1)𝑛
𝑛2
Let,
∞
𝑎0
𝑓(𝑥) = |𝑥| = + ∑ 𝑎𝑛 cos 𝑛𝑥
2
𝑛=1